Relative efficiencies of peptidylarginine deiminase 2 and 4 in generating target sites for anti-citrullinated protein antibodies in fibrinogen, alpha-enolase and histone H3 - Damgaard, Dres; Bawadekar, Mandar; Senolt, Ladislav; Stensballe, Allan; Shelef, Miriam A; Nielsen, Claus H (PLoS One, 2018)
OBJECTIVE: Peptidylarginine deiminase 2 (PAD2) and PAD4 are expressed in the synovium of rheumatoid arthritis (RA) patients and catalyze citrullination of arginine residues in proteins targeted by anti-citrullinated protein antibodies (ACPAs). Little is known about the relative importance of PAD2 and PAD4 in generating citrullinated self-antigens. Here we investigate the ability of PAD2 and PAD4 to generate citrullinated targets for ACPAs in four human proteins. METHODS: Synovial fluid (SF) and plasma were collected from 42 RA patients. Human fibrinogen, human alpha-enolase (ENO1), human histone H3, and human serum albumin (HSA) were citrullinated in vitro by PAD2 or PAD4. The total degree of citrullination was determined using the anti-modified citrulline approach. Antibody binding to native and citrullinated proteins was measured by ELISA. RESULTS: ACPAs within pooled SF from multiple RA patients reacted equally well with, and cross-reacted with, PAD2- and PAD4-citrullinated fibrinogen. ACPAs from most individual patient SF and plasma samples bound equally well to PAD2- and PAD4-citrullinated fibrinogen or ENO1. When histone H3 was used as target, PAD4 was generally superior in generating epitopes recognized by ACPAs. No binding to citrullinated HSA was observed. CONCLUSION: In most patients, PAD2 and PAD4 are equally efficient in generating citrullinated target sites for ACPAs in fibrinogen and ENO1. The binding of autoantibodies to histone H3 was generally higher after citrullination with PAD4 than with PAD2. Citrullinated HSA is not a target for ACPAs.
Keywords: fibrinogen; protilátky proti citrulinovaným peptidům; Arthritis, Rheumatoid; revmatoidní artritida; Hydrogen-Ion Concentration; Citrullination; In Vitro Techniques; techniky in vitro; lidé; Anti-Citrullinated Protein Antibodies; rekombinantní proteiny; Recombinant Proteins; citrulinace; synoviální tekutina; vápník; sérový albumin; peptidylarginindeiminasy; Calcium; Serum Albumin; Synovial Fluid; histony; Fibrinogen; Histones; Phosphopyruvate Hydratase; koncentrace vodíkových iontů; Protein-Arginine Deiminases; fosfopyruváthydratasa; Humans